2018
DOI: 10.1056/nejmoa1808561
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Outcomes after Restrictive or Liberal Transfusion for Cardiac Surgery

Abstract: In patients undergoing cardiac surgery who were at moderate-to-high risk for death, a restrictive strategy for red-cell transfusion was noninferior to a liberal strategy with respect to the composite outcome of death from any cause, myocardial infarction, stroke, or new-onset renal failure with dialysis at 6 months after surgery. (Funded by the Canadian Institutes of Health Research and others; TRICS III ClinicalTrials.gov number, NCT02042898 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
135
2
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(144 citation statements)
references
References 33 publications
2
135
2
5
Order By: Relevance
“…(AUC = 0.73; 95% CI, 0.66 to 0.78; P \ 0.001). AUC = area under the curve; CI = confidence interval The fact that more restrictive transfusion methods and lower levels of hemoglobin are becoming more acceptable during cardiac surgery 23 further emphasizes the importance of accurate point-of-care blood glucose measurements in anemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…(AUC = 0.73; 95% CI, 0.66 to 0.78; P \ 0.001). AUC = area under the curve; CI = confidence interval The fact that more restrictive transfusion methods and lower levels of hemoglobin are becoming more acceptable during cardiac surgery 23 further emphasizes the importance of accurate point-of-care blood glucose measurements in anemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality was 6.2% in the restrictive‐threshold group and 6.4% in the liberal‐threshold group (OR 0.95; 95% CI, 0.8, 1.2). There were no significant between‐group differences in the secondary outcomes after 28 days or 6 months . Intriguingly, subgroup analyses demonstrated that the restrictive strategy was associated with a lower risk of the composite outcome in patients 75 years or older, whereas the liberal strategy was associated with a lower risk of the composite outcome in patients younger than 75 years of age.…”
mentioning
confidence: 82%
“…There were no significant between-group differences in the secondary outcomes after 28 days or 6 months. 9 Intriguingly, subgroup analyses demonstrated that the restrictive strategy was associated with a lower risk of the composite outcome in patients 75 years or older, whereas the liberal strategy was associated with a lower risk of the composite outcome in patients younger than 75 years of age. The mechanism underlying a potential differential effect of age needs to be further explored as the findings were from subgroup analyses and were thus hypothesis-generating.…”
mentioning
confidence: 96%
“…In the Transfusion Requirements in Cardiac Surgery (TRICS)-3 trial, a lower Hb threshold for RBC transfusion was favoured in patients at least 75 years of age. 13,17 In contrast, in the Transfusion Requirements in Critical Care (TRICC) trial, potential benefit with a lower Hb threshold was suggested among patients younger than 55 years of age. 4 In 2 other large trials, no heterogeneous effects of different Hb thresholds for RBC transfusion were observed in patients of different ages.…”
mentioning
confidence: 99%